Pengaruh Meditasi Anapanasati terhadap Perhatian Siswa Kelas IX pada Materi Brahma Wihara di SMP Negeri 2 Keling - Wibowo, Teguh; Sujiono, Sujiono; Putranto, Dwiyono (Jurnal Simki Pedagogia, 2024)
Lack of student learning attention affects the expected learning achievement. By implementing Anapanasati meditation, it is expected to improve student attention during learning. The study was conducted at SMP Negeri 2 Keling Dk. Cungkuk, Ds. Tunahan, Kec. Keling, Kab. Jepara. The purpose of the study was to determine the effect of Anapanasati meditation on the attention of grade IX students on the Brahma Wihara material at SMP Negeri 2 Keling. This study applies the Pre-experimental method with a one group pretest-posttest Design. The study was conducted on grade IX students who are Buddhist. The pre-test and posttest data of participants were obtained using a research instrument in the form of a Likert scale. Analysis of research data using the Successive Interval Method (MSI). The results of the study showed a difference in the mean before and after being given treatment. The Pre-test mean was 41.56 and the Posttest mean was 51.06, there was a difference of 9.5. The Tcount was 12.621 and Ttable 2.119 (Tcount> Ttable) and sig.sig. (2-tailed) shows 0.000 < 0.05 indicating that there is an influence of Anapanasati meditation on student attention. From the results of the study, it was concluded